Methyl Carbamate‐Lithium Salt Deep Eutectic Electrolyte for Lithium‐Ion Batteries. Issue 15 (13th July 2022) - Hardin, Nathaniel Z.; Duca, Zachary; Imel, Adam; Ward, Patrick A.
Abstract: Deep eutectic electrolytes (DEEs) represent a burgeoning field in electrolytes for energy storage applications. Compared to the more conventionally studied Li‐ion electrolyte systems, these electrolytes offer numerous advantages, such as high ion concentration, costs, lower temperature operation, and safety. In this work, the formation of a novel eutectic electrolyte based on lithium salts and methyl carbamate was reported. These DEEs were formed via mixing lithium salts and low‐cost methyl carbamate at ratios varying from 1 : 2 to 1 : 5 (mol:mol). The DEE formed from methyl carbamate and lithium hexafluorophosphate (LiPF6 ) at a 1 : 5 molar ratio generated a 4V stability window and a 25 °C conductivity of up to 3.16E −3 S cm −1 . The DEE formed from methyl carbamate and lithium bis(trifluoromethane)sulfonimide (LiTFSI) at a 1 : 5 molar ratio generated a 3.2 V stability window and a 25 °C conductivity of up to 2.87E −3 S cm −1 . The LiPF6 DEE also demonstrated a discharge capacity of 128 mAh g −1 after 50 cycles with 93 % discharge capacity retention at moderate cycling rates of 0.5C in a lithium titanate (LTO)/lithium iron phosphate (LFP) full cell. These results demonstrate the potential for methyl carbamate to generate eutectics from lithium salts and offer alternative electrolytes for use in low‐temperature Li‐ion battery applications. Abstract : Electrolyte: A novel binary deep eutectic electrolyte was developed using lithium salts and methyl carbamate. The deep electrolyte showed promising electrochemical behavior in a lithium titanate and lithium iron phosphate full cell, allowing for stable cycling and low temperature operation.